Conservação do polvo octopus insulares (mollusca, cephalopoda) utilizando diferentes aditivos químicos - Alves, Vanessa Clarice Fernandes (Universidade Federal Rural do Semi-Árido, 2018)
The consumption of fish has been increasing in recent years and this increase may be related to the nutritional benefits that the fish brings, healthy food, low level of fats, rich in essential amino acids, high levels of protein and omega 3 and 6. Commercialization of fish in Brazil is usually aimed at selling it fresh, however, with the great demand for the product, the processing becomes indispensable, and this may compromise the final quality of the product. Therefore, the objective of this study was to compare the influence of food additives on the microbiological, physical, chemical and sensorial characteristics of Octopus insular. The samples were submitted to four treatments using aqueous solutions of distilled water (control), 5% sodium lactate (LS), 5% lactic acid (LA) and 5% sodium tripolyphosphate (TPF). We investigated mesophilic and psychrotrophic microorganisms, Salmonella and measured pH, CRA, PPC, texture, color, MIQ. The LA was the one that best inhibited the microbiological development and provided a greater alteration in the analyzes of the MIQ, the lower LS results of lipid oxidation (TBARS) and the TPF a better capacity to retain water, lower losses in cooking, greater shear force and less color variation. The results obtained exceeded the values stipulated by the national legislation for analysis of TMA, from the 12th day of storage, with the exception of LA, and remained within the limits for BVT. Among the additives tested lactic acid was the one that stood out the most, presenting a conservation of the original characteristics, in the microbiological, chemical and physical qualities during the time of storage
Keywords: Aditivos alimentares; Conservação de pescado; Conservantes químicos; Food additives; Conservation of fish; Chemical preservatives; CIENCIAS AGRARIAS::ZOOTECNIA::PRODUCAO ANIMAL